Revision of the West Palaearctic species of the genus Pales Robineau-Desvoidy (Diptera: Tachinidae) - Cerretti, Pierfilippo (Zootaxa, 2005)
A taxonomic revision of the West Palaearctic species of the genus Pales Robineau-Desvoidy is presented and the identity of the genus is defined and discussed. Pales abdita sp. nov. from some localities in the Mediterranean region and Pales marae sp. nov. from Sardinia are described, illustrated and compared with similar species. A key to the ten known West Palaearctic species of Pales is presented. The rare genus Schembria Rondani is suggested as the possible sister-group of Pales and the male genitalia of the only known species, S. meridionalis Rondani, are figured for the first time.